Strategi Guru dalam Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Pendidikan Pancasila Kelas IV di SD Negeri 5 Penatih - Ni Luh Meisa Pratiwi; Ni Nyoman Perni; Jayanthi Riva Prathiwi (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Pancasila Education is a compulsory subject taught at every level of education, from elementary to higher education, with the aim of shaping students’ attitudes and behaviors based on the values of Pancasila in their daily lives. This study aims to describe the teacher's strategies in implementing the Problem Based Learning (PBL) model to enhance students' critical thinking skills in the Pancasila Education subject for fourth-grade students at SD Negeri 5 Penatih. The research focuses on three main aspects: (1) the implementation of PBL by teachers in improving students’ critical thinking in the topic "Pancasila as the Foundation of My Country", (2) the supporting and inhibiting factors in applying the PBL model, and (3) the implications of PBL implementation on the learning process and outcomes. This study employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The findings reveal that the teacher’s strategy in applying PBL involves three key stages: planning (designing contextual and relevant problems), implementation (the teacher acting as a facilitator during group discussions), and evaluation (assessing students’ thinking processes). Supporting factors for the successful application of PBL include teacher competence, student motivation, a conducive learning environment, and curriculum support. On the other hand, limited instructional time and low student participation present challenges that need to be addressed. The implications of PBL implementation include enhanced critical thinking skills, improved collaboration abilities, and the development of student character as reflective, open-minded, and responsible individuals. Learning becomes more engaging, meaningful, and interactive as students are actively involved in solving real-life problems related to their everyday experiences.